Land reforms in India : performance and challenges in Gujarat and Maharashtra / edited by Ghanshyam Shah and D.C.Sah - "Shah, Ghanshyam(ed.)" (New Delhi, 2002)
This volume is part of an on-going series on land reforms and focuses on the states of Gujarat and Maharashtra. It analyses land reform legislation, their implementation, and the factors responsible for their success or failure. It also studies the nature and role of people's movements in building pressure on the state for land rights, the position of common property resources, the role of technology in enhancing production and equity, and the survival of the significant tribal populations.
Keywords: Land reforms-Gujarat